A Novel Allergen-Specific Immune Signature-Directed Approach to Dietary Elimination in Eosinophilic Esophagitis. Issue 12 (December 2019) - Dellon, Evan S.; Guo, Rishu; McGee, Sarah J.; Hamilton, Deanna K.; Nicolai, Emily; Covington, Jacquelyn; Moist, Susan E.; Arrington, Ashley; Wright, Benjamin L.; Burks, A. Wesley; Vickery, Brian P.; Kulis, Michael
Abstract : OBJECTIVES: Dietary elimination for treatment of eosinophilic esophagitis (EoE) is limited by lack of accuracy in current allergy tests. We aimed to develop an immunologic approach to identify dietary triggers and prospectively test allergen-specific immune signature-guided dietary elimination therapy. METHODS: In the first phase, we developed and assessed 2 methods for determining selected food triggers using samples from 24 adults with EoE: a CD4+ T-cell proliferation assay in peripheral blood and food-specific tissue IgG4 levels in esophageal biopsies. In the second phase, we clinically tested elimination diets created from these methods in a prospective cohort treated for 6 weeks (NCT02722148). Outcomes included peak eosinophil counts (eos/hpf), endoscopic findings (measured by the EoE Endoscopic Reference Score), and symptoms (measured by the EoE Symptom Activity Index). RESULTS: Parameters were optimized with a positive test on either assay, yielding agreements of 60%, 75%, 53%, 58%, and 53% between predicted and known triggers of peanut, egg, soy, wheat, and milk, respectively. In clinical testing, the mean number of foods eliminated based on the assays was 3.4, and 19 of 22 subjects were compliant with treatment. After treatment, median peak eosinophil counts decreased from 75 to 35 ( P = 0.007); there were 4 histologic responders (21%). The EoE Endoscopic Reference Score and EoE Symptom Activity Index score also decreased after treatment (4.6 vs 3.0; P = 0.002; and 32.5 vs 25.0; P = 0.06, respectively). DISCUSSION: We successfully developed a new testing approach using CD4 + T-cell proliferation and esophageal food-specific IgG4 levels, with promising accuracy rates. In clinical testing, this led to improvement in eosinophil counts, endoscopic severity, and symptoms of dysphagia, but a smaller than expected number of patients achieved histologic remission.